Occupational exposure to noise and patterns of hearing threshold among factory workers in Ibadan Nigeria (2014)
This study examined occupational exposure to noise and patterns of hearing loss among industrial workers in Ibadan, Nigeria. The study adopted an ex-post facto research design; sampling 100 participants comprising of industrial workers and sawmillers, who were assessed by means of Pure Tone Audiometry, the sound level of the factories were measured with sound level meter. Frequency count, percentage, mean, standard deviation and pearson product moment correlation were employed to answer the four research questions raised. The sound assessment revealed that the sound level in the industrial plant is higher than that of the sawmill, .and the notched pattern of hearing threshold predominated the hearing among the respondents on the left and right ears. There was positive significant relationship between age, work experience and bilateral hearing loss. Based on these findings, it was recommended that the altering of design and technology of mechanical equipments resulting in low noise emission should be put in place in factories, and that receptors of sound should be protected adequately from industrial noise.